Carbon sequestration in community forests: an eligible issue for CDM (A case study of Nainital, India) - Mandal, R.A.; van Laake, P. (Banko Janakari, 2007)
Though community forests have a vital role in environmental services and sustainable development in developing countries such as in India and Nepal, the credit cannot yet to be claimed under the Clean Development Mechanism (CDM). It is due to difficulties of assessing the biomass and carbon storage in the community forests for monitoring and verification. However, forest carbon monitoring is possible by the use of advanced technology such as Leaf Area Index (LAI) that is derived from hemispherical photographs using Gap Light Analyser by establishing the relation with the biophysical characteristics of the vegetation. Therefore, the study stepped towards the assessment of carbon sequestration in community forests using LAI. To meet research tasks, which were to establish the relationship between biomass and LAI and explore environmental benefit of community forest management approach, 70 samples from Dhaili and 73 samples from Guna Chautara community forests were collected using stratified random sampling. The sample data included girth, height and canopy photos. Canopy photographs were taken by use of hemispherical cameras. After biomass was estimated using allometric equations, LAI values from canopy photos were analyzed by the use of Gap Light Analyser. Furthermore, for relationship development, the linear regressions analyses were carried out and CDM criteria were incorporated with forest management practice. Main outputs of the research were carbon sequestration model based on LAI and justification of CDM criteria with community forest management practice. Key words: Carbon Sequestration, Leaf Area Index (LAI), Clean Development Mechanism (CDM), Community Forest, Gap Light Analyser, Hemispherical photographs Banko Janakari Vol.15(2) 2005 pp53-61